Effect of the impeller blade outlet setting angle on the performance of the helical axial-flow multiphase pump - Wang, Jiaqiong; Hu, Chen; Bai, Ling; Agarwal, Ramesh; Zhou, Ling (Frontiers in Energy Research, 2024)
As one of the core pieces of equipment in the multiphase mixing system, the helical axial-flow multiphase pump plays a vital role in the process of offshore oil extraction. In order to explore the influence of the impeller blade outlet setting angle on the internal flow of the helical axial-flow multiphase pump, this paper increases the outlet setting angle of the flow surface by −3°, −1.5°, and 1.5°, respectively, based on the original multiphase pump. It calculates the flow characteristics of the impeller with four different outlet setting angles (including the original impeller) under the design condition with different inlet gas volume fractions (GVFs = 0, 10%, 30%, 50%, and 70%) by adopting the Euler–Euler non-homogeneous flow model and SST k-ω turbulence model. Furthermore, it compares its external characteristic curve and the internal pressure, velocity, gas distribution, and other rules of change of the impeller and guide vane under higher inlet GVF conditions (50%). The results show that in the pure water state, increasing the outlet setting angle appropriately can enhance both the pressure pressurization capability and efficiency of the helical axial-flow multiphase pump; the pressure pressurization capability and efficiency of each scheme decrease with an increase in inlet GVF, and at 50%–70% inlet GVF, the option of increasing the outlet setting angle by −1.5° is better; as the blade outlet setting angle decreases, the axial cross-sectional pressure after gas–liquid mixing increases, the overall velocity distribution is more uniform, and the vortex formed due to the counter-pressure flow in the secondary guide vane is reduced; the accumulation of gas phase on the backside of the impeller and guide vanes improves, leading to a reduction in flow losses.